2014
DOI: 10.7763/ijet.2014.v6.672
|View full text |Cite
|
Sign up to set email alerts
|

Erosion Wear Behaviour of Copper Slag Filled Short Bamboo Fiber Reinforced Epoxy Composites

Abstract: Abstract-Recently, the use of natural fiber reinforced composites starts gaining popularity in engineering applications due to the fact that this material possesses characteristics that are comparable to conventional materials. Among natural fibers, bamboo has been widely used for many such applications due to its availability and low cost. Attempts have been made in this paper to explore the potential utilization of bamboo fiber in polymer matrix composites. Due to environmental regulations, new ways of utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…The reported results were in agreement with Biswas et al [120]. Inclusion of copper slag in bamboo fiber/epoxy composites were studied by Sandhyarani Biswas [121]. Lower erosion rate was observed with 15 wt% of filler content.…”
Section: Influence Of Filler Particles On Spesupporting
confidence: 88%
“…The reported results were in agreement with Biswas et al [120]. Inclusion of copper slag in bamboo fiber/epoxy composites were studied by Sandhyarani Biswas [121]. Lower erosion rate was observed with 15 wt% of filler content.…”
Section: Influence Of Filler Particles On Spesupporting
confidence: 88%
“…The work is progressing towards improving the wear and friction properties of these composites. Biswas and AnivaXess [10] investigated erosive wear behavior of bamboo-glass hybrid epoxy composite at various impingement angles and impact velocities. The result showed that hybrid composite shows minimum wear rate than neat epoxy composite and the composite behaving like semibrittle mode of erosion wear.…”
Section: Introductionmentioning
confidence: 99%
“…This test is performed according to (ASTM G76) at room temperature [20,21]. Specimens have been cut into disk shape of a diameter of (40mm) and a thickness of (5mm) [22] as represented in figure (3).…”
Section: Erosion Wear Testmentioning
confidence: 99%